2014
DOI: 10.1080/10498850.2013.787661
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical and Textural Alterations in Indian Squid (Loligo duvauceli) Mantle During Frozen Storage and Cooking

Abstract: Textural variations in squid mantle and the role of proteins on texture during frozen storage and cooking were investigated. Myofibrillar protein (62.36%) and pepsin soluble collagen (10.70%) accounted for the major fraction of total protein (22.17%). The histochemistry of mantle tissue showed a meshlike arrangement of myofibrillar proteins with a collagenous dermal layer and feebly passing collagen through myotome bundles. Texture profile analysis of unfrozen mantle suggested the first phase of hardening at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Furthermore, Fuente‐Betancourt, García‐Carreño, Navarrete del Toro, Córdova‐Murueta, and Lugo‐Sánchez () produced proteins gels from squid mantle muscle that also share comparable electrophoresis pattern than registered in our results. Moreover, Raman and Mathew () studied protein physicochemical and structural changes of cooked (at different heating temperatures) mantle muscle from Indian squid ( Loligo duvauceli ); these authors reported protein denaturation and formation of new low molecular weight proteins as evidenced in SDS‐PAGE of pre‐fractionated proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Fuente‐Betancourt, García‐Carreño, Navarrete del Toro, Córdova‐Murueta, and Lugo‐Sánchez () produced proteins gels from squid mantle muscle that also share comparable electrophoresis pattern than registered in our results. Moreover, Raman and Mathew () studied protein physicochemical and structural changes of cooked (at different heating temperatures) mantle muscle from Indian squid ( Loligo duvauceli ); these authors reported protein denaturation and formation of new low molecular weight proteins as evidenced in SDS‐PAGE of pre‐fractionated proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Peculiar organization of connective tissue network (mainly composed by collagen) and its changes induced by heating are implicated in squid meat softening; this is because collagen breakdown and/or gelatinization facilitate the collapse and detachment of muscular fibers, thus promoting loss of soluble protein (muscular and sarcoplasmic) in released water (Kugino, Kugino, & Ogawa, ). Up to this day, the influence of cooking conditions (temperatures and setting times) over structural and physicochemical properties of muscle from squid species like Sephioteuthis lessoniana, Illex illecebrosus, Loligo pealei, Todarodes sagitatus , and Illex argentinus have been studied by several researchers in order to get their optimal processing conditions (Agrafioti & Katsanidis, ; Kolodziejska, Sikorski, & Sadowska, ; Otwell & Hamann, ; Raman & Mathew, ; Stanley & Hultin, ; Stanley & Smith, ). Due to Dosidicus gigas is a highly consumable and commercial valuable specie in México and Latin‐American countries, the objective of this research was to evaluate the effect of cooking process (heating in boiling water at 100 °C during 30 min) over shrinkage, weight loss, soluble protein, water holding capacity, protein integrity (myofibril and stromal), and its structural and microscopic related changes in the squid meat with the aim to provide better efficient processing conditions in both, large industry and domestic markets.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reported molecular weights for gelatin bands vary from 45 to 100 kDa, supporting gelatization of collagen as one of the main processes occurring within the protein extracts. [25,26] Raman and Mathew [27] observed in squid muscle (Loligo duvauceli) that with cooking temperatures above 65°C, the α and β chains of collagen would undergo denaturation and protein gelatinization could occur at approximately 80°C. [28] In the present study, although protein denaturation was detected on SDS-PAGE, it was not possible to determine differences in the behavior of the PSC extracted from the different body parts studied of jumbo squid (mantle, fins, and arms) after the cooking process.…”
Section: Changes In Collagen Solubility (Cs)mentioning
confidence: 99%
“…As shown in Table S1, all the six texture indicators of the stored samples including hardness, springiness, cohesiveness, gumminess, chewiness, and resilience were positively correlated with each other. In general, there is a positive correlation among texture indicators (Gokoglu et al., 2018; Raman & Mathew, 2015; Singh & Benjakul, 2017). As shown in Table S2, all the six texture indicators were positively correlated with mercapto value and WHC, but were negatively correlated with TCA‐soluble peptide, MFI, water‐soluble Hyp, carbonyl value, disulfide bonds, surface hydrophobicity, average pore diameter, and average porosity.…”
Section: Resultsmentioning
confidence: 99%